New alternative in the treatment of rheumatoid arthritis: clinical utility of baricitinib - Kawalec P; Śladowska K; Malinowska-Lipień I; Brzostek T; Kózka M (Dove Medical Press, 2019)
Paweł Kawalec,1 Katarzyna Śladowska,2 Iwona Malinowska-Lipień,3 Tomasz Brzostek,3 Maria Kózka4 1Drug Management Department, Institute of Public Health, Faculty of Health Sciences, Jagiellonian University Medical College, Kraków, Poland; 2Department of Experimental Hematology, Institute of Zoology and Biomedical Research, Faculty of Biology and Earth Sciences, Jagiellonian University, Kraków, Poland; 3Department of Internal and Community Nursing, Institute of Nursing and Midwifery, Faculty of Health Sciences, Jagiellonian University Medical College, Kraków, Poland; 4Department of Clinical Nursing, Institute of Nursing and Midwifery, Faculty of Health Sciences, Jagiellonian University Medical College, Kraków, Poland Abstract: Baricitinib is an innovative small-molecule drug that reversibly inhibits continuous activation of JAK/STAT pathway, thus reducing joint inflammation. The drug was approved for use as monotherapy or in combination with methotrexate (MTX) in the treatment of adults with moderately to severely active rheumatoid arthritis (RA). The aim of this paper was to review the studies on pharmacology, mode of action, pharmacokinetics, efficacy, and safety of baricitinib in patients with RA. Baricitinib provides an innovative approach to modulating the immune and inflammatory response in patients with RA, which is especially important in individuals who do not respond to disease-modifying antirheumatic drugs or standard biologic drugs (tumor necrosis factor inhibitors) or who lose response over time. Baricitinib therapy reduces symptoms of RA and improves the quality of life. Moreover, it has shown high efficacy and an acceptable safety profile in Phase III randomized controlled trials (RCTs) and become another JAK inhibitor approved for RA treatment, providing a useful alternative option. RCTs have revealed a significant benefit of baricitinib over placebo, MTX, and adalimumab in terms of standard efficacy outcomes, especially the American College of Rheumatology ACR20, ACR50, and ACR70 response rates. Additionally, a clinically meaningful improvement in patient-reported outcomes, including the quality of life, compared with placebo has been reported. The safety profile seems acceptable, although some rare but potentially severe adverse events have been observed, such as serious infections, opportunistic infections (eg, herpes zoster), malignancies, and cardiac or hepatic disorders. Baricitinib administered at an approved dose of 2 or 4 mg once daily offers a novel and promising alternative to parenterally administered biologic drugs used in RA treatment. Keywords: JAK inhibitor, baricitinib, efficacy, rheumatoid arthritis, safety